Lithospheric velocity model across the Southern Central Iberian Zone (Variscan Iberian Massif): The ALCUDIA wide‐angle seismic reflection transect. Issue 3 (23rd March 2015) - Ehsan, Siddique Akhtar; Carbonell, Ramon; Ayarza, Puy; Martí, David; Martínez Poyatos, David; Simancas, José Fernando; Azor, Antonio; Ayala, Concepción; Torné, Montserrat; Pérez‐Estaún, Andrés
Abstract A P wave seismic velocity model has been obtained for the Central Iberian Zone, the largest continental fragment of the Iberian Variscan Belt. The spatially dense, high‐resolution, wide‐angle seismic reflection experiment, ALCUDIA‐WA, was acquired in 2012 across central Iberia, aiming to constrain the lithospheric structure and resolve the physical properties of the crust and upper mantle. The seismic transect, ~310 km long, crossed the Central Iberian Zone from its suture with the Ossa‐Morena Zone to the southern limit of the Central System mountain range. The energy generated by five shots was recorded by ~900 seismic stations. High‐amplitude phases were identified in every shot gather for the upper crust (Pg and PiP) and Moho (PmP and Pn). In the upper crust, the P wave velocities increase beneath the Cenozoic Tajo Basin. The base of the upper crust varies from ~13 km to ~20 km between the southernmost Central Iberian Zone and the Tajo Basin. Lower crustal velocities are more homogeneous. From SW‐NE, the traveltime of PmP arrivals varies from ~10.5 s to ~11.8 s, indicating lateral variations in the P wave velocity and the crustal thickness, reflecting an increase toward the north related with alpine tectonics and the isostatic response of the crust to the orogenic load. The results suggest that the high velocities of the upper crust near the Central System might correspond to igneous rocks and/or high‐grade metamorphic rocks. The contrasting lithologies and the increase in the Moho depth to the north evidence differences in the Variscan evolution.